Emerging role of gut microbiota dysbiosis in neuroinflammation and neurodegeneration - Solanki, Riddhi; Karande, Anjali; Ranganathan, Prathibha (Frontiers in Neurology, 2023)
Alzheimer's disease (AD), is a chronic age-related progressive neurodegenerative disorder, characterized by neuroinflammation and extracellular aggregation of Aβ peptide. Alzheimer's affects every 1 in 14 individuals aged 65 years and above. Recent studies suggest that the intestinal microbiota plays a crucial role in modulating neuro-inflammation which in turn influences Aβ deposition. The gut and the brain interact with each other through the nervous system and chemical means via the blood-brain barrier, which is termed the Microbiota Gut Brain Axis (MGBA). It is suggested that the gut microbiota can impact the host's health, and numerous factors, such as nutrition, pharmacological interventions, lifestyle, and geographic location, can alter the gut microbiota composition. Although, the exact relationship between gut dysbiosis and AD is still elusive, several mechanisms have been proposed as drivers of gut dysbiosis and their implications in AD pathology, which include, action of bacteria that produce bacterial amyloids and lipopolysaccharides causing macrophage dysfunction leading to increased gut permeability, hyperimmune activation of inflammatory cytokines (IL-1β, IL-6, IL-8, and NLRP3), impairment of gut- blood brain barrier causing deposition of Aβ in the brain, etc. The study of micro-organisms associated with dysbiosis in AD with the aid of appropriate model organisms has recognized the phyla Bacteroidetes and Firmicutes which contain organisms of the genus Escherichia, Lactobacillus, Clostridium, etc., to contribute significantly to AD pathology. Modulating the gut microbiota by various means, such as the use of prebiotics, probiotics, antibiotics or fecal matter transplantation, is thought to be a potential therapeutic intervention for the treatment of AD. This review aims to summarize our current knowledge on possible mechanisms of gut microbiota dysbiosis, the role of gut brain microbiota axis in neuroinflammation, and the application of novel targeted therapeutic approaches that modulate the gut microbiota in treatment of AD.